KEPRIBADIAN TERBUKA GENERASI MILENIAL YANG DIPERKUAT OLEH RESILIENSI INDIVIDU MEMPENGARUHI PENINGKATAN PENGAMBILAN RESIKO INVESTASI - Ahmad Syaiful Affa; Muhammad Tsanial Aif (LPPM Universitas Pekalongan, 2022)
The dominance of the millennial generation in investing in the capital market shows the awareness of the millennial generation about financial freedom. Some mistakes in investing can cause losses to investors. When investors experience losses, they must immediately get up and return to their original condition. The ability of resilience should be able to help the millennial generation to bounce back when their investments fail. Previous studies have shown that there is a strong relationship between personality and decision making. Resilience here is a moderating factor that is considered capable of giving the effect of weakening or strengthening the personality. Based on data obtained from 109 millennial respondents in Indonesia, the results show that the open personality factor (extrovert and open to experience) affects investment risk taking, but in this study resilience has not been proven to be able to significantly moderate the relationship between open personality factors and risk taking. Data obtained by questionnaire method and tested by SEM-PLS method with R2 result of 26%.